Bone mineral density, thyroid function, and gonadal status in young adult survivors of childhood cancer - Latoch, Eryk; Muszyńska-Rosłan, Katarzyna; Panas, Agata; Panasiuk, Anna; Rutkowska-Żelazowska, Beata; Konstantynowicz, Jerzy; Krawczuk-Rybak, Maryna (Contemporary Oncology/Współczesna Onkologia, 2015)
Introduction : During the last years, changes in the diagnosis and treatment have caused a significant increase of the number of young adults who experienced cancer in childhood. This enlarging population is affected by many health problems, including multiple hormone deficiencies and bone mineral deficits. This is the first polish study assessing bone mineral density and endocrine status in young adult cancer survivors. Material and methods : A total of 76 long-term survivors treated for pediatric cancer were identified. The mean age at the time of study was 24.1 ±3.5 years. Bone mineral density and TSH, fT3, fT4, FSH, LH, estradiol and testosterone level were assessed for each patient. Results : Nine subjects were diagnosed with subclinical hypothyroidism. We found higher level of TSH in the study group, in comparison with control group (p = 0.015). Eighteen patients had increased level of FSH. In the study group higher number of patients with high FSH level was found in comparison with the control group (p = 0.049). A low BMD was observed in 7 patients whereas mild BMD deficits were found in 19 participants. Conclusions : In conclusion, our data show that young adult cancer survivors might experienced various hormonal problems including low bone mass, thyroid impairment and gonadal dysfunction. Some of the patients required treatment, but they were not diagnosed before this study. There is the lack of proper clinical assessment among adult childhood cancer survivors in Poland. Therefore, we demonstrated the need for a comprehensive plan for longitudinal follow-up for late effects in these population.